PENILAIAN DAN PEMILIHAN VENDOR DENGAN PENDEKATAN METODE AHP DALAM INDUSTRI RETAIL - der, Ivan (Jurnal Tekno, 2020)
Vendor assessment and selection are an essential thing, especially in the retail industry. A qualified vendor will help retail industry to achieve competitive price, product with high quality, deliver good services and an excellent delivery.  This study aims to create a new system and standardisation in vendor assessment and selection to help the procurement department in procuring process. Analytic Hierarchy Process (AHP) method was used in this study to determine weight for each assessment sub-category.  The Decision Support System (DSS) in spreadsheet used to help decision makers in determining which vendor should be maintained in their vendor list. This study applied in one of retail companies in Jakarta. Price, terms of payment, quality, delivery time and quantity, lead time product and responsiveness in taking return products are the factors that have been considered in vendor assessment and selection. The results of this study show that vendor X6, X10, X11, X12, X14 and X16 should not be maintained as retail vendor list.Vendor assessment and selection are an essential thing, especially in the retail industry. A qualified vendor will help retail industry to achieve competitive price, product with high quality, deliver good services and an excellent delivery.  This study aims to create a new system and standardisation in vendor assessment and selection to help the procurement department in procuring process. Analytic Hierarchy Process (AHP) method was used in this study to determine weight for each assessment sub-category.  The Decision Support System (DSS) in spreadsheet used to help decision makers in determining which vendor should be maintained in their vendor list. This study applied in one of retail companies in Jakarta. Price, terms of payment, quality, delivery time and quantity, lead time product and responsiveness in taking return products are the factors that have been considered in vendor assessment and selection. The results of this study show that vendor X6, X10, X11, X12, X14 and X16 should not be maintained as retail vendor list.